Fine Sieving of Atmospheric Particles in a Collected Air Sample Using Oil Electrophoresis - Xinyue Li; Siyu Xu; Maosheng Yao (Aerosol and Air Quality Research)
Abstract To solve the challenge of extracting nano- to micrometer-sized atmospheric particles from a mixed sample, we developed an electrostatic sieve system, the Fine Sieving of Collected Atmospheric Particles using Oil Electrophoresis (iSCAPE), based on the application of an electrostatic field to a non-conductive mineral oil. Using atmospheric samples, which were collected from different cities, in addition to soil and road dust samples, we tested this system under different conditions and found that the “iSCAPE’d” particles moved rapidly at varying velocities and in two opposite directions. The diverse origins of the sample—ambient air, soil, or road dust—exhibited specific charged properties, and clearly affected the electrical mobility, as demonstrated by the graphs, of the particles following the “iSCAPEing,” which lasted from seconds to minutes. We also observed an increased abundance of particles in specific mobility ranges. Furthermore, according to our adenosine triphosphate (ATP) monitoring results, the iSCAPE is capable of separating bacterial particles by size and electrical mobility. The experimental data suggests that the iSCAPE relies heavily on the electrostatic field strength, mineral oil viscosity, and run time. In theory, this method can extract any targets from a complex sample, thus creating many research opportunities in environmental, biomedical, and life sciences.